Paramedic ethics, capacity and the treatment of vulnerable patients. (2nd December 2020) - Moritz, Dominique; Ebbs, Phillip; Carver, Hamish
Abstract : Vulnerable patients are at an increased risk of harm or exploitation in healthcare. Their vulnerability may impede their autonomy, which can then affect their ability to self-advocate. Clinicians have an important role in supporting vulnerable patients and upholding their autonomy. This article explores practical issues of capacity, autonomy and beneficence as they apply to some of the most common vulnerable groups that UK paramedics may encounter: children, older people, those with a mental illness and persons with a disability.